(untitled) (Eurasian Medical Research Periodical, 2022)
Recent studies point to probiotics as a promising option for fighting biofilms. Probiotics are live microorganisms which, when administered in sufficient quantities, are of health benefit to the host. Lactobacillus is the dominant group of bacteria with proven probiotic effect, where Lactobacillus is more effective. The current study aimed to study effects of Lactobacillus acidophilus on Staphylococcus aureus.It was observed in this study the Lactobacillus acidophilus broth culture appeared inhibitory activity against isolates of Staphylococcus. While the supernatant did not give inhibitory activity except for the isolate of Staph1.Also,it was observed that the biofilm of all methicillin-resistant S. aureus isolates using Lactobacillus acidophilus broth showed significant differences compared to control. In addition, the scanning electron microscope results showed a decrease in the thickness of the biofilm after treatment with L. acidophilus